Optimalisasi Pengembangan Desa Wisata Baha Berbasis Pendampingan - Dewa Putu Oka Prasiasa (WIDYABHAKTI Jurnal Ilmiah Populer, 2021)
The development of a tourism village is expected to be an alternative in overcoming the problem of saturation with the demand for tourism products. One of the tourism villages that was developed to provide solutions to these problems is the Baha Tourism Village. In fact, the Baha Tourism Village has not been optimally developed. Based on this phenomenon, research with qualitative methods was carried out. The results showed that to optimize the development of Baha Tourism Village, higher education assistance is needed by implementing five priorities. Of the five priorities planned to optimize the development of Baha Tourism Village, the first priority to the third priority have been running, while the fourth priority and the fifth priority have not yet been implemented. In the third priority, there are three ongoing activities funded by the 2020 Baha Village Fund, namely making trash bins along the trekking / cycling route, making banners along the trekking / cycling path, and making 50 sanggah catu (a place to pray in the fields).While the nine activities that have not been running are in the third priority, namely making entrance ticket booths, making gazebos, making lelakut, making sunari, making maps or maps of trekking / cycling paths, repairing or maintaining trekking / cycling paths, procurement of garbage transporting motors, procuring sensor machines for lawn mowing, and the manufacturing of the CHSE facility.